Pengembangan Multimedia Interaktif Berbasis Website Pada Pembelajaran Biologi Materi Sistem Pernapasan - Darmayanti, Nur Aulia; St. Syamsudduha; Syahriani, Syahriani (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2023)
This research and development (R & D) aims to develop media in the form of website-based interactive multimedia on learning the biology of the respiratory system and to determine the level of validity, practicality, and effectiveness of the media. This research used the ADDIE model with five stages: analysis, design, development, implementation, and evaluation. The instruments used were validation sheets, student questionnaires, educator questionnaires, and learning outcomes tests. The data was analyzed for validity, practicality, and effectiveness. The results show that website-based interactive multimedia met the very valid category with an average validator rating of 3.5. The practicality of web-based interactive multimedia meets the very practical category with an average of 3.6. Interactive multimedia on websites is highly effective in improving student learning outcomes, with a completion rate of 85.5%. In summary, Website-based interactive multimedia is suitable for learning because the media is valid, practical, and effective.